Complete mitochondrial genome of Sinocyclocheilus yishanensis (Cypriniformes: Cyprinidae) and phylogenetic position - Fuguang Luo; Jie Huang; Guofan Shi; Tong Luo; Junling Liu; Yanhong Wen (Mitochondrial DNA. Part B. Resources, 2019)
Sinocyclocheilus yishanensis belongs to the genus Sinocyclucheilus (Cypriniformes, Cyprinidae), endemic to Guangxi province, Southwestern China. The circular mitogenome was 16,573 bp in length and consisted of 13 protein-coding genes, two ribosomal RNA (rRNA) genes, 22 transfer RNA (tRNA) genes, and one non-coding control region. The overall base composition was 31.83% A, 25.14% T, 27.03% C, and 16.00% G with 43.03% GC content. Phylogenetic analysis using mitochondrial genomes of 16 species showed that all Sinocyclocheilus species clustered as one monophyletic clade except S. jii, and S. yishanensis was the closest to S. ronganensis.